Exercise interventions for nonspecific low back pain: a bibliometric analysis of global research from 2018 to 2023 - Zang, Wanli; Yan, Jin (Frontiers in Medicine, 2024)
Objective This study aims to explore global research trends on exercise interventions for nonspecific low back pain from 2018 to 2023 through bibliometric analysis. Methods A systematic search was conducted in the Web of Science Core Collection database to select relevant research articles published between 2018 and 2023. Using CiteSpace and VOSviewer, the relationships and impacts among publications, different countries, journals, author groups, references, and keywords were analyzed in depth. Results The bibliometric analysis included 4,896 publications, showing a trend of initial growth followed by a decline. At the national level, the United States made the most significant contributions in this field. The journal “Lancet” had three of the top 10 most-cited articles, with an average citation count of 306.33, and an impact factor reaching 168.9 in 2023. The analysis also revealed that “disability,” “prevalence,” and “management” were high-frequency keywords beyond the search terms, while “rehabilitation medicine,” “experiences,” and “brain” emerged as new hotspots in the research. Conclusion This study reveals the global trends in research on exercise interventions for nonspecific low back pain over the past 5 years and highlights potential research frontiers in the field. These findings provide a solid foundation for focusing on key issues, potential collaboration directions, and trends in research development in the future, offering valuable references for further in-depth studies.